Children’s Psychosocial Narratives in “Found Childhoods" - Phoenix, Ann (Narrative Works, 2020)
This paper focuses on a proliferating narrative genre: videos where children are central, posted on the internet for public consumption. The video analyzed is of a pre-school U.S. Black girl resisting how her mother has combed her hair. It offers insights into family practices and display (Finch, 2007; Morgan, 2011) that would usually not be open to scrutiny and cannot be captured in the same way in interviews. The paper argues that the videoed narrative can only be understood if the sociocultural context of racism and contestation over the denigration of Black girls’ and women’s Afro hair is analyzed.